Challenging the justice of a basic income policy when focusing on the homeless population: A case study on Germany - Verena Löffler (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2024)
In a given society, those who are least advantaged would allegedly benefit the most from receiving a basic income. However, the merits of such a policy are generally debated according to the effects on society as a whole, not specifically on the most marginalized; thus, the potential benefits of a basic income for marginalized groups is unclear. To address this gap, I identify homeless people in Germany as the least advantaged and assess how this group would be impacted by a basic income based on real libertarian, liberal egalitarian, and republican theories of justice. Specifically, I show how introducing a basic income would affect the homeless population in Germany in terms of income, self-respect, and power. While a basic income could increase most of the homeless population's income and improve communal relations, the stigma attached to homelessness will only decrease insofar as the basic income policy helps people exit homelessness. Moreover, a basic income would decrease power imbalances between the homeless population and state agencies, but the policy's effects on relations between homeless persons and fellow citizens, particularly landlords, are ambiguous. This article contributes to the theoretical discussion on a basic income, providing a new concern about whether such a policy is fair to the homeless population. Moreover, this article is relevant in practice, as the discussed effects may prompt avenues for designing future social policies that address the homeless population as the most vulnerable group in modern welfare states.
Keywords: D31; D63; H55; I32; I38; 330; basic income; homelessness; public policy; social justice